Features of Polypharmacy in Dutch Older Outpatients with Personality Disorders: A Cross-sectional Study - Schulkens, Julie E. M.; P. J. Van Alphen, Sebastiaan (bas); R. J. Verhey, Frans; Sobczak, Sjacko (European Journal of Mental Health, 2024)
Introduction: Pharmacotherapy in older adults with personality disorders (PDs) can be even more complicated compared to younger adults, because older adults stand at risk for polypharmacy and its negative consequences due to somatic comorbidities and biological age-related changes.Aims: This study’s primary objective serves to describe the point prevalence of polypharmacy in older adults with PDs. Next, we described 1) the number of psychotropics employed, 2) classes of psychotropics, 3) the number of somatic medication, and 4) the anticholinergic burden of the total medication.Methods: This cross sectional study was performed at a clinical center of excellence for older adults with PDs in the Netherlands. Fifty outpatients aged 65 years and older with a primary diagnosis of a PD were selected from an alphabetically ordered list. Data from the files on polypharmacy (use of five medications or more daily), use of medication and the anticholinergic burden (ARS score) was collected.Results: Polypharmacy was present in 72% of older adults with PDs. The mean number of psychotropics was 2.0 (SD 1.4) psychotropics per person, for somatic medication the mean was 6.2 (SD 3.6). Antidepressants were the most frequently prescribed (used by 62%), followed by anxiolytics (used by 40%). The mean ARS score was 1.1 points (SD 1.7).Conclusions: The prevalence of polypharmacy in older adults with PDs stands high, due to the high use of both psychotropics and somatic medication. Although this study provides important and new information on the use of medication in older adults, its representation of the population may be limited due to the tertiary care setting and small sample size excluding certain PDs (e.g., schizoid or obsessive-compulsive PD). Also, we did not register or measure the consequences of polypharmacy.